GR‐α and GR‐β mRNA levels in peripheral blood mononuclear cells of acute myelitis patients can assist in the identification of glucocorticoid sensitivity and are correlated with glucocorticoid therapeutic effect. (22nd June 2022) - Tang, Bolin; Han, Jun; Wang, Fen; Li, Xiang; Zhao, Chaoyang
Abstract : Abstract: Acute myelitis (AM) is a rare neuro‐immune spinal cord disease. This study sought to explore the transcription level of glucocorticoid (GC) receptors α and β (GR‐α/GR‐β) in peripheral blood mononuclear cells (PBMCs) and their correlation with GC efficacy and sensitivity in AM patients. AM patients were grouped into the GC‐sensitive group ( N  = 80) and GC‐refractory group ( N  = 67). The GR‐α and GR‐β mRNA levels in PBMCs were detected. The differentiating value of GR‐α, GR‐β, and GR‐α + GR‐β on GC sensitivity and resistance in AM patients was assessed. The independent correlation between GR‐α and GR‐β mRNA levels and GC sensitivity in AM patients, t and the correlation between GR‐α and GR‐β mRNA levels and spinal function after GC treatment were analyzed. GR‐α mRNA level in PBMCs of GC‐refractory patients was lower than that of GC‐sensitive patients, while GR‐β mRNA level was higher than that of GC‐sensitive patients. GR‐α + GR‐β mRNA had a high diagnostic value for GC sensitivity and resistance in AM patients (area under the ROC curve = 0.881, sensitivity = 79.1%, specificity = 85.0%). GR‐α and GR‐β mRNA levels were independently correlated with GC sensitivity. GR‐α and GR‐β mRNA levels were correlated with the spinal function of AM patients after GC treatment. Overall, GR‐α and GR‐β mRNA levels in PBMCs of AM patients can assist in the identification of GC sensitivity and are correlated with GC efficacy.